Checklist of freshwater fishes from Loreto, Peru - Meza-Vargas, Vanessa (2021)
This study presents an extensive review of published and unpublished occurrence records of fish species in the Loreto department. Located in the northeast of the country, Loreto is the most geographically extensive region in the Peruvian territory. Despite the increase in fish collections in Loreto in recent years, the ichthyofauna of this department needs to be more documented. Based on a database of scientific collections and bibliographic information, an updated checklist of the freshwater fishes from Loreto is presented. The results reveal a rich and diversified ichthyofauna, with 873 species distributed in 331 genera, 50 families and 15 orders. The main groups are Characiformes (42.6%), Siluriformes (34.8%), Gymnotiformes (8.6%) and Cichliformes (7.4%). Part of the ichthyofauna has restricted distribution for Loreto (4.7%). In addition, 9.0% of species from Loreto are used in fisheries. Meanwhile, 219 species (25%) were categorized according to the IUCN criteria where only six species (0.7%) are currently considered threatened species (CR, EN or VU). The results presented in this work indicate that this department needs more studies to know the biodiversity of fish, likewise, the information presented constitutes a contribution to the knowledge of fish diversity that would support environmental management actions and decision-making aimed at conserving one of the most diverse departments of Peru.